A Radiolucent Foreign Body Ingestion as a Cause of Acute Dysphagia (Bangladesh Journal of Medical Science, 2018)
Foreign body denture is common among edentulous adults because of decrease the sensitivity of the oral cavity. Carelessness in handling dentures and failure to seek early medical attention even the denture has broken are among the contributing factors. Persistence of symptoms with normal radiograph findings still require further actions which include surgical intervention. Rigid esophagoscopy remain as standard treatment modality for removal of foreign body.Bangladesh Journal of Medical Science Vol.17(3) 2018 p.515-517